2010
DOI: 10.1111/j.1747-4477.2010.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial leakage of GuttaFlow‐filled root canals compared with Resilon/Epiphany and Gutta‐percha/AH26‐filled root canals

Abstract: The purpose of this study was to assess bacterial apical leakage in root canals obturated with GuttaFlow and compare this with the leakage of root canals obturated with Resilon/Epiphany or Gutta-percha/AH26. A total of 55 single-rooted human teeth were divided randomly into three experimental (n = 15) and two control groups (n = 5). Following a standardised preparation, the teeth were obturated with either GuttaFlow, Resilon/Epiphany or Gutta-percha/AH26. A two-chamber bacterial model using Enterococcus faecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Various bacteria have been used in microleakage studies [17][18]21,25 . However, there is a focus on E. faecalis because of its resistance [19][20]22,24 , survival in nutrient-poor areas over long periods 26 , and association with persistent chronic periapical lesions 27 . The results demonstrated that the mean time of leakage in samples in the experimental period was 21 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various bacteria have been used in microleakage studies [17][18]21,25 . However, there is a focus on E. faecalis because of its resistance [19][20]22,24 , survival in nutrient-poor areas over long periods 26 , and association with persistent chronic periapical lesions 27 . The results demonstrated that the mean time of leakage in samples in the experimental period was 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have used single-rooted teeth [17][18][19][20][21][22][23][24] . The use of molars was proposed due to their high incidence in endodontic treatment, and the choice of the distobuccal root of the maxillary molar was based on a standardization criterion 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,38,39 However, other investigations have indicated that some obturation systems like Guttaflow and Resilon cones with Epiphany provide better seal against microbial leakage than gutta-percha/AH-plus sealer. 40-43 , However, greater amount of microleakage has been reported with Resilon compared to gutta-percha/zinc oxide eugenol and AH-plus.…”
Section: Introductionmentioning
confidence: 99%
“…Resilon™ has been subjected to numerous studies to determine if its sealing abilities are superior to GP, and these studies have utilised various methods of assessing leakage. A recent bacterial leakage study by Kangarlou et al 84 noted no significant differences between Resilon™/Epiphany™ and GP/AH26™. Oliveira et al 85 also conducted bacterial leakage studies with GP and various sealers as well as with the Resilon™/Epiphany™ system.…”
Section: Resin-based Obturation Systemsmentioning
confidence: 99%